META-ANALYSIS OF THE EFFECT OF LEARNING INTERVENTION TOWARD MATHEMATICAL THINKING ON RESEARCH AND PUBLICATION OF STUDENT - Kadir Kadir (TARBIYA: Journal of Education in Muslim Society, 2017)
Abstract The purpose of this study was to analyse the effect of mathematics learning intervention on students' mathematical thinking ability. The research method used survey of thesis of the student. The effect of studies applying learning to mathematical thinking was done using meta-analysis techniques. The research finding that research conducted by students by providing learning intervention was able to improve students' mathematical thinking ability. Aspects of mathematical thinking ability include connection ability, communication, representation, problem-solving, logical, critical, creative, analytical, generalization, quantitative, and adaptive thinking. The types of research used by students are dominated by the experiment with mix-method approach and classroom action research. Other methods, research development. The research and publication at the Department of Mathematics Education, Faculty of Educational Sciences have adapted to the trend of mathematics education research on the national and international level. Abstrak Tujuan penelitian ini adalah menganalisis efektivitas pengaruh intervensi pembelajaran matematika terhadap kemampuan berpikir matematis siswa. Metode penelitian yang digunakan adalah survei terhadap skripsi dan publikasi mahasiswa. Pengaruh  penelitian-penelitian yang menerapkan pembelajaran terhadap kemampuan berpikir matematis dianalisis dengan teknik meta-analisis. Temuan penelitian mengungkapkan bahwa secara keseluruhan penelitian-penelitian yang dilakukan mahasiswa dengan memberikan intervensi pembelajaran ternyata mampu meningkatkan kemampuan berpikir matematis siswa. Aspek kemampuan berpikir matematika yang meliputi: kemampuan koneksi, komunikasi, representasi, pemecahan masalah, kemampuan berpikir: logis, kritis, kreatif, reflektif, intuitif, penalaran: analalogi, generalisasi, kuantitatif, kreatif, dan adaptif. Metode penelitian yang digunakan mahasiswa didominasi metode eksperimen dengan pendekatan mix-method dan penelitian tindakan kelas. Disamping itu terdapat beberapa mahasiswa  memilih metode penelitian pengembangan. Hasil penelitian dan publikasi pada Program Studi Pendidikan Matematika telah menyesuaikan dengan tren penelitian pendidikan pendidikan matematika baik pada level nasional maupun internasional. How to Cite : Kadir. (2017). Meta-Analysis of the Effect of Learning Intervention Toward Mathematical Thinking on Research and Publication of Student. TARBIYA: Journal of Education in Muslim Society, 4(2), 162-175. doi:10.15408/tjems.v4i2.8010. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v4i2.8010